High-Fidelity Hugoniots of α Phase RDX Solid from High-Quality Force Field with Thermal, Zero-Point Vibration, and Anharmonic Effects - 宋华杰 李华 黄风雷 张树道 洪滔 (Chinese physics letters, 2015)
It is shown that the introduction of thermal effect, zero-point vibration, and phonon anharmonicity to a high quality and first-principle-Sased force field （atomic potential） results in a significant improvement in predict- ing the densities for the α phase crystalline hexahydro-1,3,5-trinitro-l,3,5-triazine （RDX）, and derivation of its high-fidelity Hugoniot locus and Mie-Grfineisen equation of state covering a very wide range of pressures and temperatures. This work can be used to efficiently and accurately predict the thermophysical properties of solid explosives over the pressures and temperatures to which they are subjected, which is a long-standing issue in the field of energetic materials.